Analisis Makna Dalam Tradisi Haul Syeikh Abdul Wahab Rokan Al-khalidi An-Naqsyabandi - Nurul Dini Hanifah; Putri Indriani; Nursukma Suri (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This study analyzes the meanings contained in the dhikr recited during the haul tradition of Sheikh Abdul Wahab Rokan Al-Khalidi An-Naqsyabandi in Besilam, Langkat. The research employs a qualitative descriptive method with an anthropolinguistic approach, utilizing Roland Barthes' semiotic theory, which distinguishes between denotative (literal) and connotative (symbolic) meanings. The aim of this study is to explore the depth of the dhikr's meanings within the spiritual and cultural context of the Islamic community, particularly in relation to the Naqsyabandiyah order. The findings indicate that these prayers possess two dimensions of meaning: the literal meaning related to seeking forgiveness from Allah, honoring the Prophet, and glorifying Allah, and a deeper connotative meaning that encompasses symbolic understandings such as strengthening the spiritual connection with Allah, the Prophet Muhammad, and the saints, as well as fostering a collective consciousness among Muslims. Overall, this haul tradition serves not only as a tribute to the deceased but also as a means to reinforce faith, remind participants of the importance of compassion, and maintain the continuity of teachings and blessings passed down from the Prophet Muhammad SAW to his succeeding saints.